2023
DOI: 10.3390/antibiotics12121736
|View full text |Cite
|
Sign up to set email alerts
|

Could an Optimized Joint Pharmacokinetic/Pharmacodynamic Target Attainment of Continuous Infusion Piperacillin-Tazobactam Be a Valuable Innovative Approach for Maximizing the Effectiveness of Monotherapy Even in the Treatment of Critically Ill Patients with Documented Extended-Spectrum Beta-Lactamase-Producing Enterobacterales Bloodstream Infections and/or Ventilator-Associated Pneumonia?

Milo Gatti,
Matteo Rinaldi,
Tommaso Tonetti
et al.

Abstract: (1) Background: Piperacillin-tazobactam represents the first-line option for treating infections caused by full- or multi-susceptible Enterobacterales and/or Pseudomonas aeruginosa in critically ill patients. Several studies reported that attaining aggressive pharmacokinetic/pharmacodynamic (PK/PD) targets with beta-lactams is associated with an improved microbiological/clinical outcome. We aimed to assess the relationship between the joint PK/PD target attainment of continuous infusion (CI) piperacillin-tazob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Importantly, previous preclinical studies showed that PK/PD target attainment of C min /MIC ratios ranging between 3.8 and 6.2 with beta-lactams was effective in preventing the emergenge of breakthrough resistance to beta-lactams among Gram-negatives [ 38 ]. This represented a first rationale for starting the adoption of an aggressive PK/PD target of 100% f T >4x MIC in clinical practice, as recently reported by several studies [ 6 , 28 , 29 ]. Scheduled timing for assessing aggressive PK/PD target attainment of beta-lactams may be crucial, especially in case of severe infections.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Importantly, previous preclinical studies showed that PK/PD target attainment of C min /MIC ratios ranging between 3.8 and 6.2 with beta-lactams was effective in preventing the emergenge of breakthrough resistance to beta-lactams among Gram-negatives [ 38 ]. This represented a first rationale for starting the adoption of an aggressive PK/PD target of 100% f T >4x MIC in clinical practice, as recently reported by several studies [ 6 , 28 , 29 ]. Scheduled timing for assessing aggressive PK/PD target attainment of beta-lactams may be crucial, especially in case of severe infections.…”
Section: Discussionmentioning
confidence: 80%
“…The aggressive beta-lactam PK/PD target selected in the different studies was a 100% f T >4x MIC and/or C ss or C min /MIC ratio > 4 in 18/21 studies [ 6 , 15 , 20 24 , 26 36 ], and a 100% f T >5x MIC and/or C ss or C min /MIC ratio > 5 in 3/21 studies [ 7 , 25 , 37 ]. Joint PK/PD target was assessed in three studies evaluating BL/BLIc (namely piperacillin-tazobactam, ceftazidime-avibactam, and meropenem-vaborbactam) [ 15 , 28 , 29 ]. In 11/21 studies, the assessment of aggressive PK/PD target attainment of beta-lactams was assessed first within 72 h from starting treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent retrospective study carried out among 43 ICU critically ill patients having documented Gram-negative BSI and/or ventilator-associated pneumonia, we showed that the TDM-guided attainment of optimal joint PK/PD target of CI piperacillin–tazobactam monotherapy granted very high microbiological eradication rates (87.4%) and resulted in protection against microbiological failure (OR 0.03; 95%CI 0.003–0.27; p = 0.002) [ 53 ]. Although in that study the number of patients having ESBL-producing Enterobacterales infections was quite limited (only 6/43), the findings allowed us to hypothesize that this strategy could have been potentially effective even when dealing with ESBL producers [ 53 ].…”
Section: Discussionmentioning
confidence: 99%